The Impact of Posttraumatic Stress Disorder on the 6-Month Outcomes in Collaborative Care Management for Depression - Kurt B. Angstman; Alberto Marcelin; Cesar A. Gonzalez; Tara K. Kaufman; Julie A. Maxson; Mark D. Williams (SAGE Publishing, 2016)
Posttraumatic stress disorder (PTSD) has symptoms that exist along a spectrum that includes depression and the 2 disorders may coexist. Collaborative care management (CCM) has been successfully used in outpatient mental health management (especially depression and anxiety) with favorable outcomes. Despite this, there exist limited data on clinical impact of a diagnosis of PTSD on depression outcomes in CCM. The present study used a retrospective cohort design to examine the association of PTSD with depression outcomes among 2121 adult patients involved in CCM in a primary care setting. Using standardized self-report measures, baseline depression scores and 6-month outcome scores were evaluated. Seventy-six patients had a diagnosis of PTSD documented in their electronic medical record. Patients with PTSD reported more severe depressive symptoms at baseline (Patient Health Questionnaire-9 score of 17.9 vs 15.4, P < .001) than those without PTSD. Controlling for sociodemographic and clinical characteristics, a clinical diagnosis of PTSD was associated with lower odds (AOR = 0.457, CI = 0.274-0.760, P = .003) of remission at 6 months and was also associated with higher odds (AOR = 3.112, CI = 1.921-5.041, P < .001) of persistent depressive symptoms at 6 months after CCM. When coexisting with depression, a diagnosis of PTSD was associated with worse depression outcomes, when managed with CCM in primary care. Opportunities still exist for more aggressive management of depression in these patients to help improve remission as well as reduce persistent depressive symptoms.